Legal Protection of Digital Design Works Sold on E-Commerce Digital Platforms - Ega Haidar Afif; Marsitiningsih Marsitiningsih (Jurnal Impresi Indonesia, 2024)
The development of digital technology means that creators can now use e-commerce platforms to sell their digital design works. However, the ease of access and digital nature of these designs raises concerns about potential copyright infringement. This is an article on the legal protection of digital design works sold on digital e-commerce platforms. Digital intellectual property, such as logos, illustrations, and icons, must be protected. In today's internet age, creators use e-commerce platforms as one of the main ways to sell their works to customers around the world. However, the ease of access and digital nature of these design works make copyright infringement easier. The researcher used normative legal research. Research with normative methods is conducted by examining literature sources as secondary data. In normative legal research, literature documents serve as a foundation of information to serve the research field. This research data is categorized as secondary data because it is obtained from a collection of rule-based literature reviews. especially intellectual property rights law, especially copyright and copyright of online magazines and digital works. The results show that digital design itself gets protection against ownership of intellectual property rights and gets exclusive rights to its creation for the creator. Efforts to resolve graphic design copyright issues; temporary legal remedies, civil legal remedies, and criminal legal remedies.